1987
DOI: 10.1073/pnas.84.23.8257
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exocyclic substituents of purine bases on DNA curvature.

Abstract: Complementary oligonucleotides with 5' overhanging deoxyguanosine or deoxycytidine stretches, re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 42 publications
5
50
0
Order By: Relevance
“…This observation indicates that the cleavage pattern of a particular sequence can be significantly affected by the substitution of only a few nucleotides. This last observation is consistent with previous work (Diekmann et al 1987;Koo and Crothers 1987), which demonstrated that single nucleotides substituted for adenine in the center of an A-tract sequence could completely abolish the curvature of that DNA molecule, therefore drastically changing the overall shape and structure as the result of a modest change in sequence.…”
Section: Degeneracy Of Hydroxyl Radical Cleavage Data Patternssupporting
confidence: 81%
“…This observation indicates that the cleavage pattern of a particular sequence can be significantly affected by the substitution of only a few nucleotides. This last observation is consistent with previous work (Diekmann et al 1987;Koo and Crothers 1987), which demonstrated that single nucleotides substituted for adenine in the center of an A-tract sequence could completely abolish the curvature of that DNA molecule, therefore drastically changing the overall shape and structure as the result of a modest change in sequence.…”
Section: Degeneracy Of Hydroxyl Radical Cleavage Data Patternssupporting
confidence: 81%
“…My NMR results also correlate well with gel electrophoresis studies which measured the extent of DNA bending in oligomers containing the site AAAAA:TTTTT, where variants were made containing one or more I»C substitutions (Diekmann et al, 1987;Koo & Crothers, 1987). (Pelton, 1990).…”
Section: Basesupporting
confidence: 54%
“…The exocyclic groups of DNA would be expected to affect the mechanics of bending in two ways. First, their presence could exercise constraints on the compressibility of both the major and the minor grooves (27), more especially at extreme, protein-induced deformations. Second, addition or loss of the purine 2-amino group, by altering the number of hydrogen bonds in a base pair, also will affect the rotational freedom of the substituted bases about the long axis of the base FIG.…”
Section: Discussionmentioning
confidence: 99%
“…We observe that nucleosomal particles assembled with I-, UI-, and IM-substituted DNAs all possess high amplitudes of hydroxylradical cleavage modulation. In addition, these same DNA species are characterized by an increased apparent intrinsic curvature, possibly because of the stacking of an I-C or I-M base pair on adjacent A-T pairs, thus creating the structural equivalent of a short dA:dT tract (27,(32)(33)(34). Indeed, recent crystal structures have shown that single I-C base pairs sandwiched between A-T pairs in the sequence AIA exhibit the high propeller twist normally characteristic of A-T but not G-C base pairs (32).…”
Section: Fig 4 Exocyclic Groups Affect the Rotational Positioning Omentioning
confidence: 99%